Electrode for non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2020188708
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-11-12
AI Technical Summary
【0009】 本発明の一形態に係る非水電解質二次電池用電極によれば、優れた出力特性を発揮することができる。
Smart Images

Figure 0007629712000002 
Figure 0007629712000003 
Figure 0007629712000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, the spread of various electric vehicles is expected to help solve environmental and energy problems. Secondary batteries have been developed as on-board power sources for driving motors, etc., which are key to the spread of these electric vehicles. As secondary batteries, non-aqueous electrolyte secondary batteries, which are expected to have high energy density and high output, have been attracting attention.
[0003] As a technique for obtaining a battery with high energy density and high output, Patent Document 1 discloses an electrode that uses a gelling agent as a binder for a carbon-based active material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-281162 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the inventors of the present invention conducted an investigation and found that a battery using the technology described in Patent Document 1 does not provide sufficient output characteristics.
[0006] Therefore, an object of the present invention is to provide an electrode for a non-aqueous electrolyte secondary battery capable of exhibiting excellent output characteristics. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that it is effective to use fibrous carbon having a large aspect ratio as a conductive assistant in an electrode active material layer constituting an electrode, and have completed the present invention.
[0008] That is, the electrode for a non-aqueous electrolyte secondary battery according to the present invention has a current collector and an electrode active material layer, which is a non-binding body arranged on the surface of the current collector. Here, the electrode active material layer contains an electrode active material, a conductive assistant, and a gel-forming polymer, the conductive assistant being fibrous carbon having an aspect ratio of 1000 or more, the gel-forming polymer being at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HEP), polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol dimethacrylate, polypropylene glycol diacrylate, and copolymers thereof, and the content of the gel-forming polymer in the electrode active material layer is more than 0 mass% and less than 4 mass% with respect to the total solid content of 100 mass%. Effect of the Invention
[0009] Advantageous Effects of Invention According to an electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention, excellent output characteristics can be exhibited. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view showing a schematic overall structure of a stacked (flat) non-bipolar (internal parallel connection) secondary battery according to one embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view illustrating a bipolar secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One embodiment of the present invention is an electrode for a non-aqueous electrolyte secondary battery having a current collector and an electrode active material layer that is a non-binding body arranged on the surface of the current collector. Here, the electrode active material layer contains an electrode active material, a conductive assistant, and a gel-forming polymer, the conductive assistant being fibrous carbon having an aspect ratio of 1000 or more, the gel-forming polymer being at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HEP), polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol dimethacrylate, polypropylene glycol diacrylate, and copolymers thereof, and the content of the gel-forming polymer in the electrode active material layer is more than 0 mass% and less than 4 mass% with respect to the total solid content of 100 mass%. The electrode for a non-aqueous electrolyte secondary battery of this embodiment can exhibit excellent output characteristics.
[0012] Although the detailed mechanism by which the above-mentioned effects are achieved is unclear, it is presumed as follows: Note that the technical scope of the present invention is in no way limited to the following mechanism.
[0013] In this embodiment, the retention of the electrode can be improved by using fibrous carbon having an aspect ratio of 1000 or more as the conductive assistant. Therefore, an electrode can be formed even with an amount of gel-forming polymer that cannot be used to form an electrode with a conductive assistant such as acetylene black (for example, 2 mass% (see Comparative Example 3)), and it is considered that the decrease in electron transferability and effective ion conductivity in the electrode due to the gel-forming polymer excessively covering the electrode active material can be suppressed. As a result, it is considered that the internal resistance can be reduced and excellent output characteristics can be exhibited. Furthermore, since an electrode can be formed with a smaller amount of gel-forming polymer, it is considered that a larger amount of electrode active material can be contained, and the energy density can also be improved.
[0014] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the claims and is not limited to the following embodiments. The dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios. In this specification, the range "X to Y" means "X or more and Y or less." Furthermore, unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.
[0015] FIG. 1 is a schematic cross-sectional view illustrating a schematic overall structure of a flat (stacked) non-bipolar (internal parallel connection) secondary battery (hereinafter also simply referred to as a “stacked secondary battery”) according to one embodiment of the present invention.
[0016] As shown in Fig. 1, the stacked secondary battery 10a of this embodiment has a structure in which a substantially rectangular power generating element 21, in which a charge / discharge reaction actually proceeds, is sealed inside a laminate film 29. Here, the power generating element 21 has a configuration in which a positive electrode in which a positive electrode active material layer 13 is arranged on both sides of a positive electrode collector 11', an electrolyte layer 17 made of a separator containing an electrolytic solution, and a negative electrode in which a negative electrode active material layer 15 is arranged on both sides of a negative electrode collector 12 are laminated. Specifically, the negative electrode, the electrolyte layer, and the positive electrode are laminated in this order such that one positive electrode active material layer 13 and the adjacent negative electrode active material layer 15 face each other with the electrolyte layer 17 interposed therebetween.
[0017] As a result, the adjacent positive electrode, electrolyte layer, and negative electrode constitute one unit cell layer 19. Therefore, the stacked secondary battery 10a shown in FIG. 1 can be said to have a configuration in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel. The positive electrode current collectors of the outermost layers located on both outermost layers of the power generating element 21 each have the positive electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. That is, instead of using a current collector dedicated to the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as the current collector of the outermost layer as it is. Also, by reversing the arrangement of the positive electrode and the negative electrode from FIG. 1, the outermost negative electrode current collector may be located on both outermost layers of the power generating element 21, and the negative electrode active material layer may be disposed on one or both sides of the outermost negative electrode current collector.
[0018] A positive electrode current collector 25 and a negative electrode current collector 27 that are electrically connected to the electrodes (positive and negative electrodes) are attached to the positive electrode current collector 11' and the negative electrode current collector 12, respectively, and are structured to be sandwiched between the ends of the laminate film 29 and led out of the laminate film 29. The positive electrode current collector 25 and the negative electrode current collector 27 may be attached to the positive electrode current collector 11' and the negative electrode current collector 12 of the electrodes by ultrasonic welding, resistance welding, or the like, respectively, via a positive electrode terminal lead and a negative electrode terminal lead (not shown) as necessary.
[0019] Fig. 2 is a cross-sectional view showing a bipolar secondary battery according to another embodiment of the present invention. The bipolar secondary battery 10b shown in Fig. 2 has a structure in which a substantially rectangular power generating element 21, in which the charge / discharge reaction actually proceeds, is sealed inside a laminate film 29 that is a battery exterior body. In this specification, the bipolar lithium ion secondary battery may also be simply referred to as a "bipolar secondary battery," and an electrode for a bipolar lithium ion secondary battery may also be simply referred to as a "bipolar electrode."
[0020] As shown in FIG. 2, the power generating element 21 of the bipolar secondary battery 10b of this embodiment has a plurality of bipolar electrodes 23 in which a positive electrode active material layer 13 electrically coupled to one surface of a current collector 11 is formed, and a negative electrode active material layer 15 electrically coupled to the opposite surface of the current collector 11 is formed. The bipolar electrodes 23 are stacked with an electrolyte layer 17 interposed therebetween to form the power generating element 21. In this case, the bipolar electrodes 23 and the electrolyte layer 17 are alternately stacked so that the positive electrode active material layer 13 of one bipolar electrode 23 and the negative electrode active material layer 15 of the other bipolar electrode 23 adjacent to the one bipolar electrode 23 face each other with the electrolyte layer 17 interposed therebetween. That is, the electrolyte layer 17 is sandwiched and disposed between the positive electrode active material layer 13 of one bipolar electrode 23 and the negative electrode active material layer 15 of the other bipolar electrode 23 adjacent to the one bipolar electrode 23.
[0021] The adjacent positive electrode active material layer 13, electrolyte layer 17, and negative electrode active material layer 15 constitute one single cell layer 19. Therefore, it can be said that the bipolar secondary battery 10b has a configuration in which the single cell layers 19 are stacked. In addition, a seal part (insulating layer) 31 is arranged on the outer periphery of the single cell layer 19. This prevents liquid junctions due to leakage of the electrolyte from the electrolyte layer 17, and prevents contact between adjacent current collectors 11 in the battery and short circuits caused by slight unevenness of the ends of the single cell layers 19 in the power generation element 21. The positive electrode active material layer 13 is formed on only one side of the outermost current collector 11a on the positive electrode side, which is located at the outermost layer of the power generation element 21. The negative electrode active material layer 15 is formed on only one side of the outermost current collector 11b on the negative electrode side, which is located at the outermost layer of the power generation element 21.
[0022] 2, a positive electrode current collector (positive electrode tab) 25 is disposed adjacent to the outermost current collector 11a on the positive electrode side, and extends out from the laminate film 29 that is the battery exterior body. Meanwhile, a negative electrode current collector (negative electrode tab) 27 is disposed adjacent to the outermost current collector 11b on the negative electrode side, and similarly extends out from the laminate film 29.
[0023] The number of times that unit cell layers 19 are stacked is adjusted according to the desired voltage. In bipolar secondary battery 10b, the number of times that unit cell layers 19 are stacked may be reduced if sufficient output can be ensured even if the thickness of the battery is made as thin as possible. In bipolar secondary battery 10b as well, it is preferable to have a structure in which power generating element 21 is vacuum-encapsulated in laminate film 29, which is the battery exterior body, and positive electrode current collector 25 and negative electrode current collector 27 are exposed to the outside of laminate film 29 in order to prevent external impacts and environmental deterioration during use.
[0024] According to one aspect of the present invention, there is provided a non-aqueous electrolyte secondary battery having the electrode for a non-aqueous electrolyte secondary battery of the present invention. When the non-aqueous electrolyte secondary battery has the electrode of the present aspect, the battery can exhibit excellent output characteristics.
[0025] Hereinafter, main components of the nonaqueous electrolyte secondary battery according to one embodiment of the present invention will be described.
[0026] [electrode] The electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention has a current collector and an electrode active material layer, which is a non-binding material, disposed on the surface of the current collector. The electrode of this embodiment may be used as a positive electrode or a negative electrode. When the electrode of this embodiment is used as a positive electrode, a known electrode can be used as the negative electrode. When the electrode of this embodiment is used as a negative electrode, a known electrode can be used as the positive electrode.
[0027] [Current collector] The current collector has a function of mediating the movement of electrons from one surface in contact with the positive electrode active material layer to the other surface in contact with the negative electrode active material layer. There are no particular limitations on the material constituting the current collector, but for example, metals and conductive resins can be used.
[0028] Specifically, metals include aluminum, nickel, iron, stainless steel, titanium, and copper. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, or a plated material of a combination of these metals can be preferably used. Also, a foil in which a metal surface is coated with aluminum, or a carbon-coated aluminum foil may be used. Among them, aluminum, stainless steel, copper, and nickel are preferred from the viewpoint of electronic conductivity and battery operating potential.
[0029] The latter conductive resin may be a conductive polymer material or a non-conductive polymer material to which a conductive filler is added as necessary. Examples of conductive polymer materials include polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylenevinylene, polyacrylonitrile, and polyoxadiazole. Such conductive polymer materials have sufficient conductivity even without the addition of conductive fillers, and are therefore advantageous in terms of facilitating the manufacturing process or reducing the weight of the current collector.
[0030] Examples of non-conductive polymeric materials include polyethylene (PE; high density polyethylene (HDPE), low density polyethylene (LDPE), etc.), polypropylene (PP), polyethylene terephthalate (PET), polyethernitrile (PEN), polyimide (PI), polyamideimide (PAI), polyamide (PA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyvinylidene fluoride (PVdF), polystyrene (PS), etc. Such non-conductive polymeric materials can have excellent electric potential resistance or solvent resistance.
[0031] A conductive filler may be added to the conductive polymer material or non-conductive polymer material as necessary. In particular, when the resin serving as the base material of the current collector is made of only a non-conductive polymer, a conductive filler is necessarily required to impart conductivity to the resin.
[0032] The conductive filler can be used without any particular limitation as long as it is a material having electrical conductivity. For example, metals and conductive carbons can be mentioned as materials having excellent electrical conductivity, potential resistance, or lithium ion blocking properties. The metal is not particularly limited, but preferably contains at least one metal selected from the group consisting of Ni, Ti, Al, Cu, Pt, Fe, Cr, Sn, Zn, In, Sb, and K, or an alloy or metal oxide containing these metals. The conductive carbon is also not particularly limited. Preferably, it contains at least one selected from the group consisting of acetylene black, Vulcan (registered trademark), Black Pearl (registered trademark), carbon nanofiber, Ketjen Black (registered trademark), carbon nanotube, carbon nanohorn, carbon nanoballoon, and fullerene.
[0033] The amount of conductive filler added is not particularly limited as long as it is an amount that can impart sufficient conductivity to the current collector, and is generally about 5 to 80 mass %.
[0034] The current collector may be a single layer structure made of a single material, or may be a laminate structure made of a suitable combination of layers made of these materials. From the viewpoint of reducing the weight of the current collector, it is preferable that the current collector includes at least a conductive resin layer made of a resin having electrical conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector.
[0035] [Electrode active material layer] The electrode active material layer is disposed on the surface of the current collector and is a non-binding material containing an electrode active material, a conductive assistant, and a gel-forming polymer. "A non-binding material containing an electrode active material, a conductive assistant, and a gel-forming polymer" means that the electrode active materials are not fixed to each other by a binder.
[0036] The binder content in the electrode active material layer is preferably 1 mass% or less, more preferably 0.5 mass% or less, even more preferably 0.2 mass% or less, particularly preferably 0.1 mass% or less, and most preferably 0 mass%, relative to 100 mass% of the total solid content in the electrode active material layer.
[0037] In this specification, whether or not the active material layer is a non-bound body of the electrode active material can be confirmed by observing whether or not the active material layer collapses when the active material layer is completely immersed in an electrolyte solution. When the active material layer is made of a bound body containing an electrode active material, it can maintain its shape for one minute or more, but when the active material layer is a non-bound body containing an electrode active material, the shape collapses in less than one minute.
[0038] In the electrode active material layer according to the present embodiment, the content of the gel-forming polymer is more than 0% by mass and less than 4% by mass with respect to 100% by mass of the total solid content. Therefore, the electrode active materials are not fixed relative to each other by the gel-forming polymer according to the present embodiment. Therefore, the gel-forming polymer according to the present embodiment is not included in the definition of the binder.
[0039] (Cathode active material) Examples of the positive electrode active material include lithium-transition metal composite oxides such as LiMn2O4, LiCoO2, LiNiO2, Li(Ni-Mn-Co)O2, and those in which a part of these transition metals is replaced by other elements, lithium-transition metal phosphate compounds, and lithium-transition metal sulfate compounds. In some cases, two or more positive electrode active materials may be used in combination. Preferably, from the viewpoint of capacity and output characteristics, lithium-transition metal composite oxides are used as the positive electrode active material. More preferably, composite oxides containing lithium and nickel are used. More preferably, Li(Ni-Mn-Co)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter also simply referred to as "NMC composite oxides"), or lithium-nickel-cobalt-aluminum composite oxides (hereinafter also simply referred to as "NCA composite oxides") are used. NMC composite oxides have a layered crystal structure in which lithium atomic layers and transition metal (Mn, Ni, and Co are arranged in an orderly manner) atomic layers are alternately stacked with oxygen atomic layers interposed therebetween. Furthermore, one Li atom is contained per atom of the transition metal M, and the amount of Li that can be extracted is twice that of spinel-type lithium manganese oxide, meaning that the supply capacity is doubled, resulting in high capacity.
[0040] As described above, the NMC composite oxide also includes composite oxides in which a part of the transition metal element is replaced by another metal element. In this case, the other elements include Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, Zn, etc., preferably Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, more preferably Ti, Zr, P, Al, Mg, Cr, and even more preferably Ti, Zr, Al, Mg, Cr from the viewpoint of improving cycle characteristics.
[0041] Since the NMC composite oxide has a high theoretical discharge capacity, it is preferable to use the NMC composite oxide represented by the general formula (1): Li a Ni b Mn c Co d M xO2 (wherein, in the formula, a, b, c, d, and x satisfy 0.9 ≦ a ≦ 1.2, 0 < b < 1, 0 ≦ c ≦ 0.5, 0 < d ≦ 0.5, 0 ≦ x ≦ 0.3, and b + c + d + x = 1. M is at least one element selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr). Here, a represents the atomic ratio of Li, b represents the atomic ratio of Ni, c represents the atomic ratio of Mn, d represents the atomic ratio of Co, and x represents the atomic ratio of M. From the viewpoint of cycle characteristics, in the general formula (1), it is preferably 0.4 ≦ b ≦ 0.6. The composition of each element can be measured, for example, by inductively coupled plasma (ICP) emission spectrometry.
[0042] Generally, nickel (Ni), cobalt (Co), and manganese (Mn) are known to contribute to capacity and output characteristics from the viewpoints of improving the purity of the material and improving electron conductivity. Ti, etc. are those that partially substitute transition metals in the crystal lattice. From the viewpoint of cycle characteristics, it is preferable that a part of the transition element is substituted by another metal element, and particularly preferably 0 < x ≦ 0.3 in the general formula (1). The crystal structure is stabilized by the solid solution of at least one selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. As a result, it is considered that the capacity reduction of the battery can be prevented even when charge and discharge are repeated, and excellent cycle characteristics can be realized.
[0043] As a more preferable embodiment, in the general formula (1), b, c, and d being 0.44 ≦ b ≦ 0.51, 0.27 ≦ c ≦ 0.31, and 0.19 ≦ d ≦ 0.26 is preferable from the viewpoint of improving the balance between capacity and life characteristics. For example, LiNi 0.5 Mn 0.3 Co 0.2 O2 is LiCoO2, LiMn2O4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3It has a larger capacity per unit mass than O2, etc. This makes it possible to improve the energy density, and has the advantage of being able to create compact, high-capacity batteries, which is also favorable from the perspective of driving range.
[0044] In addition, a more preferred embodiment is LiNi 0.8 Co 0.1 Al 0.1 O2 and LiNi 0.8 Co 0.15 Al 0.05 O2 is preferred.
[0045] From the viewpoint of achieving high output, the average particle size of the positive electrode active material is preferably 1 to 100 μm, and more preferably 1 to 20 μm. In this specification, the average particle size is measured by a particle size distribution measuring device using a laser diffraction / scattering method.
[0046] (Negative electrode active material) Examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and lithium-transition metal composite oxides (e.g., Li4Ti5O 12 ), metal materials (tin, silicon), silicon-containing alloy-based negative electrode materials (e.g., Si 60 Sn 10 Ti 30 ), lithium alloy-based negative electrode materials (for example, lithium-tin alloy, lithium-silicon alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.). In some cases, two or more types of negative electrode active materials may be used in combination. From the viewpoint of capacity and output characteristics, silicon-containing alloy-based negative electrode materials, carbon materials, lithium-transition metal composite oxides, and lithium alloy-based negative electrode materials are preferably used as the negative electrode active materials. Of course, negative electrode active materials other than those mentioned above may be used.
[0047] The average particle size of the negative electrode active material is not particularly limited, but from the viewpoint of achieving high output, it is preferably 1 to 100 μm, more preferably 1 to 20 μm.
[0048] The content of the electrode active material in the electrode active material layer is, for example, 60% by mass or more and less than 100% by mass, relative to 100% by mass of the total solid content, and from the viewpoint of output characteristics, is preferably 80% by mass or more and 99% by mass or less, more preferably more than 95% by mass and 99.5% by mass or less, and even more preferably 96% by mass or more and 98% by mass or less.
[0049] (Conductive assistant) The conductive assistant has a function of forming an electron conduction path (conductive passage) in the electrode active material layer. When such an electron conduction path is formed in the electrode active material layer, the internal resistance of the battery is reduced, which can contribute to improving the output characteristics at a high rate. In particular, it is preferable that at least a part of the conductive assistant forms a conductive passage that electrically connects the two main surfaces of the electrode active material layer (in this embodiment, a conductive passage that electrically connects from the first main surface in contact with the electrolyte layer side of the electrode active material layer to the second main surface in contact with the current collector side is formed). By having such a form, the electron transfer resistance in the thickness direction in the electrode active material layer is further reduced, so that the output characteristics at a high rate of the battery can be further improved. Note that whether or not at least a part of the conductive assistant forms a conductive passage that electrically connects the two main surfaces of the electrode active material layer (in this embodiment, a conductive passage that electrically connects from the first main surface in contact with the electrolyte layer side of the electrode active material layer to the second main surface in contact with the current collector side is formed) can be confirmed by observing the cross section of the electrode active material layer using an SEM or an optical microscope.
[0050] In the electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention, the conductive assistant is fibrous carbon having an aspect ratio of 1000 or more. By using such fibrous carbon, the electrode moldability due to the entanglement of the fibers is improved, so that the electrode can be formed with a smaller amount of gel-forming polymer. In particular, by using fibrous carbon having an aspect ratio of 1000 or more, the electrode moldability can be improved without occupying extra space in the electrode.
[0051] Examples of fibrous carbon include carbon nanotubes (single-walled carbon nanotubes and multi-walled carbon nanotubes), carbon nanofibers, vapor-grown carbon fibers, electrospun carbon fibers, polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, etc. From the viewpoint of electrical conductivity, the carbonaceous carbon is preferably carbon nanotubes.
[0052] In this specification, the aspect ratio of fibrous carbon means the average value of the ratio of the length to the diameter of 100 fibrous carbon fibers randomly selected by scanning electron microscope (SEM).
[0053] From the viewpoint of being able to reduce the amount of gel-forming polymer used, the lower limit of the aspect ratio of the fibrous carbon is preferably 1500 or more, more preferably 2500 or more, and even more preferably 3000 or more. The upper limit of the aspect ratio of the fibrous carbon is not particularly limited, and may be, for example, 20000 or less, 10000 or less, 5000 or less, or 4000 or less.
[0054] The diameter and length of the fibrous carbon are not particularly limited as long as they satisfy an aspect ratio of 1000 or more. The diameter of the fibrous carbon is, for example, 1 to 100 nm. The length of the fibrous carbon is, for example, 1 to 100 μm.
[0055] From the viewpoint of further improving the output characteristics, the content of fibrous carbon having an aspect ratio of 1000 or more in the electrode active material layer is preferably more than 0 mass% and less than 2 mass%, and more preferably 0.5 to 1.5 mass%, relative to 100 mass% of the total solid content.
[0056] Needless to say, conductive assistants other than those mentioned above may be used as long as they do not impair the effects of the present invention.
[0057] (Gel-forming polymer) The gel-forming polymer is an ion-conductive polymer, and can form a structure together with the electrode active material to play a role in ion conduction. The gel-forming polymer is at least one selected from the group consisting of polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVdF-HEP), polymethyl methacrylate (PMMA), polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol dimethacrylate, polypropylene glycol diacrylate, polymethyl methacrylate, and copolymers thereof.
[0058] From the viewpoint of further enhancing output characteristics, the gel-forming polymer is preferably selected from polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVdF-HEP) and polymethyl methacrylate (PMMA), and more preferably polyvinylidene fluoride-hexafluoropropylene (PVdF-HEP).
[0059] The content of the gel-forming polymer in the electrode active material layer is more than 0% by mass and less than 4% by mass with respect to 100% by mass of the total solid content. By the content of the gel-forming polymer being within the above range, the electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention can reduce the internal resistance, and therefore can exhibit excellent output characteristics. In addition, since the electrode can be formed with a smaller amount of gel-forming polymer, a larger amount of the electrode active material can be contained, and the energy density can also be improved.
[0060] The upper limit of the gel-forming polymer content may be 3.8% by mass or less, 3.6% by mass or less, 3.4% by mass or less, or 3.2% by mass or less, based on 100% by mass of the total solid content. The lower limit of the gel-forming polymer content may be 0.2% by mass or more, 0.4% by mass or more, 0.6% by mass or more, or 0.8% by mass or more, based on 100% by mass of the total solid content.
[0061] The content of the gel-forming polymer in the electrode active material layer is preferably 1 to 3 mass %, and more preferably 2 mass % or less, relative to 100 mass % of the total solid content, from the viewpoint of further improving the output characteristics.
[0062] (electrolyte) The electrode active material layer may further include an electrolyte solution. The electrolyte solution functions as a carrier for lithium ions. The electrolyte solution has a form in which a lithium salt is dissolved in a non-aqueous solvent.
[0063] Examples of non-aqueous solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), propylene carbonate (PC), butylene carbonate (BC), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL). Among these, from the viewpoint of further improving the rapid charging characteristics and output characteristics, the non-aqueous solvent is preferably a chain carbonate, more preferably at least one selected from the group consisting of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and more preferably selected from ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).
[0064] Examples of the lithium salt include Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3. Among these, the lithium salt is preferably Li(FSO2)2N from the viewpoints of battery output and charge / discharge cycle characteristics.
[0065] The concentration of the lithium salt in the electrolyte is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.2 mol / L.
[0066] The electrolyte may further contain additives other than the above-mentioned components. Specific examples of such compounds include ethylene carbonate, vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and 1-ethyl-2-vinylethylene carbonate. Examples of the additives include ethylene carbonate, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyl oxyethylene carbonate, methylene ethylene carbonate, and 1,1-dimethyl-2-methylene ethylene carbonate. These additives may be used alone or in combination of two or more. The amount of additive used in the electrolyte solution may be appropriately adjusted.
[0067] The thickness of the electrode active material layer is preferably 10 to 1500 μm for the positive electrode active material layer. The thickness of the negative electrode active material layer is preferably 10 to 1500 μm. If the thickness of the electrode active material layer is equal to or greater than the above-mentioned lower limit, the energy density of the battery can be sufficiently increased. On the other hand, if the thickness of the electrode active material layer is equal to or less than the above-mentioned upper limit, the structure of the electrode active material layer can be easily maintained.
[0068] The porosity of the electrode active material layer is preferably 20 to 50%, more preferably 22 to 40%, and further preferably 24 to 35%. When the porosity of the electrode active material layer is within the above-mentioned range, the contact between the electron conductive materials (conductive assistant, electrode active material, etc.) in the electrode active material layer can be sufficiently maintained, and an increase in electron transfer resistance can be prevented. As a result, the charge / discharge reaction can be uniformly progressed throughout the electrode active material layer (particularly in the thickness direction). The porosity of the electrode active material layer can be determined by measuring the weight per unit area of the electrode active material layer, measuring the thickness of the electrode active material layer using a micrometer, and calculating the pore volume from the density of each material.
[0069] Among the components of the nonaqueous electrolyte secondary battery according to the preferred embodiment of the present invention, the electrodes have been described in detail above. However, for the other components, conventionally known knowledge can be appropriately referred to.
[0070] [Electrolyte layer] The electrolyte layer according to this embodiment is preferably disposed between the electrodes and has a configuration in which a separator is impregnated with an electrolytic solution.
[0071] The electrolyte solution constituting the electrolyte layer may be the one described in the above (Electrolyte Solution). From the viewpoint of exerting the effects of the present invention, it is preferable to use the same non-aqueous solvent constituting the electrolyte solution as the non-aqueous solvent constituting the electrolyte solution contained in the electrode active material layer.
[0072] The separator constituting the electrolyte layer has a function of retaining the electrolyte to ensure lithium ion conductivity between the positive electrode and the negative electrode, and also a function of acting as a partition between the positive electrode and the negative electrode.
[0073] The separator may be in the form of, for example, a porous sheet separator made of a polymer or fiber capable of absorbing and retaining the electrolyte, or a nonwoven fabric separator.
[0074] As the separator of the porous sheet made of polymer or fiber, for example, a microporous (microporous membrane) can be used. Specific forms of the porous sheet made of the polymer or fiber include, for example, polyolefins such as polyethylene (PE) and polypropylene (PP); laminates of a plurality of these laminates (for example, a laminate having a three-layer structure of PP / PE / PP), polyimide, aramid, hydrocarbon resins such as polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), glass fibers, etc., and microporous (microporous membrane) separators can be mentioned.
[0075] The thickness of the microporous (microporous membrane) separator cannot be unequivocally defined because it varies depending on the application. For example, in applications such as motor-driven secondary batteries for electric vehicles (EVs), hybrid electric vehicles (HEVs), and fuel cell vehicles (FCVs), the thickness is preferably 4 to 60 μm for single or multi-layered structures. The micropore diameter of the microporous (microporous membrane) separator is preferably 1 μm or less at maximum (usually a pore diameter of about several tens of nm).
[0076] As the nonwoven fabric separator, conventionally known materials such as cotton, rayon, acetate, nylon, polyester, polyolefins such as PP and PE, polyimide, aramid, etc. are used alone or in combination. The bulk density of the nonwoven fabric is not particularly limited as long as sufficient battery characteristics can be obtained by the impregnated polymer gel electrolyte. The thickness of the nonwoven fabric separator is the same as that of the electrolyte layer, and is preferably 5 to 200 μm, and particularly preferably 10 to 100 μm.
[0077] In addition, the separator is preferably a separator in which a heat-resistant insulating layer is laminated on a porous substrate (separator with heat-resistant insulating layer). The heat-resistant insulating layer is a ceramic layer containing inorganic particles and a binder. The separator with heat-resistant insulating layer is one having high heat resistance, with a melting point or thermal softening point of 150°C or higher, preferably 200°C or higher. By having a heat-resistant insulating layer, the internal stress of the separator, which increases when the temperature rises, is alleviated, so that a heat shrinkage suppression effect can be obtained. As a result, it is possible to prevent the induction of short circuits between the electrodes of the battery, resulting in a battery configuration in which performance deterioration due to temperature rise is unlikely to occur. In addition, by having a heat-resistant insulating layer, the mechanical strength of the separator with heat-resistant insulating layer is improved, and the separator is unlikely to break. Furthermore, due to the heat shrinkage suppression effect and high mechanical strength, the separator is unlikely to curl during the battery manufacturing process.
[0078] The inorganic particles in the heat-resistant insulating layer contribute to the mechanical strength and thermal contraction suppression effect of the heat-resistant insulating layer. There are no particular limitations on the material used as the inorganic particles. Examples include oxides (SiO2, Al2O3, ZrO2, TiO2), hydroxides, and nitrides of silicon, aluminum, zirconium, and titanium, as well as composites thereof. These inorganic particles may be derived from mineral resources such as boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, and mica, or may be artificially produced. In addition, only one type of these inorganic particles may be used alone, or two or more types may be used in combination. Of these, from the viewpoint of cost, it is preferable to use silica (SiO2) or alumina (Al2O3), and it is more preferable to use alumina (Al2O3).
[0079] The weight of the heat-resistant particles is not particularly limited, but is preferably 5 to 15 g / m 2 Within this range, sufficient ion conductivity can be obtained, and this is preferable in terms of maintaining heat resistance.
[0080] The binder in the heat-resistant insulating layer serves to bond the inorganic particles to each other and to bond the inorganic particles to the resin porous substrate layer, ensuring stable formation of the heat-resistant insulating layer and preventing peeling between the porous substrate layer and the heat-resistant insulating layer.
[0081] The binder used in the heat-resistant insulating layer is not particularly limited, and for example, compounds such as carboxymethylcellulose (CMC), polyacrylonitrile, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene-butadiene rubber (SBR), isoprene rubber, butadiene rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), and methyl acrylate can be used as the binder. Among these, it is preferable to use carboxymethylcellulose (CMC), methyl acrylate, or polyvinylidene fluoride (PVDF). These compounds may be used alone or in combination of two or more.
[0082] The binder content in the heat-resistant insulating layer is preferably 2 to 20% by mass relative to 100% by mass of the heat-resistant insulating layer. When the binder content is 2% by mass or more, the peel strength between the heat-resistant insulating layer and the porous substrate layer can be increased, and the vibration resistance of the separator can be improved. On the other hand, when the binder content is 20% by mass or less, the gaps between the inorganic particles are appropriately maintained, and sufficient lithium ion conductivity can be ensured.
[0083] The heat shrinkage rate of the separator with heat-resistant insulation layer is 2gf / cm at 150℃. 2 It is preferable that both MD and TD are 10% or less after 1 hour of storage under these conditions. By using such a highly heat-resistant material, it is possible to effectively prevent the separator from shrinking even if the heat generation increases and the internal temperature of the battery reaches 150°C. As a result, it is possible to prevent the induction of short circuits between the battery electrodes, resulting in a battery configuration that is less susceptible to performance degradation due to temperature rise.
[0084] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a lithium ion secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 25 and the negative electrode current collector plate 27 may be made of the same material or different materials.
[0085] [Positive and negative leads] Although not shown, the current collector 11 and the current collector plate (25, 27) may be electrically connected via a positive electrode lead and a negative electrode lead. As the constituent materials of the positive electrode and the negative electrode lead, materials used in known lithium ion secondary batteries may be similarly adopted. Note that the part removed from the exterior is preferably covered with a heat-resistant insulating heat shrink tube or the like so as not to come into contact with peripheral devices or wiring, causing a current leak and affecting products (e.g., automobile parts, particularly electronic devices, etc.).
[0086] [Sealing part] The sealing portion (insulating layer) 31 is a member specific to bipolar secondary batteries (series stacked batteries) and has a function of preventing leakage of electrolyte from the electrolyte layer. The sealing portion 31 also has a function of preventing contact between current collectors and short circuit at the end of the unit cell layer. The material constituting the sealing portion may be any material that has insulation properties, sealing properties against the falling off of solid electrolyte, sealing properties against moisture permeation from the outside (sealing properties), heat resistance under the battery operating temperature, and the like. For example, acrylic resin, urethane resin, epoxy resin, polyethylene resin, polypropylene resin, polyimide resin, rubber (ethylene-propylene-diene rubber: EPDM), and the like may be used. Also, isocyanate-based adhesives, acrylic resin-based adhesives, cyanoacrylate-based adhesives, and the like may be used, and hot melt adhesives (urethane resin, polyamide resin, polyolefin resin), and the like may be used. Among these, from the standpoints of corrosion resistance, chemical resistance, ease of production (film-forming ability), and economy, polyethylene resin and polypropylene resin are preferably used as constituent materials for the insulating layer, and it is preferable to use a resin copolymerized with ethylene, propylene, and butene, with amorphous polypropylene resin as the main component.
[0087] [Battery exterior] As the battery exterior body, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum that can cover the power generating element as shown in Figs. 1 and 2 can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, an aluminate laminate is more preferable as the exterior body because the group pressure applied to the power generating element from the outside can be easily adjusted and the thickness of the electrolyte layer can be easily adjusted to the desired thickness.
[0088] The nonaqueous electrolyte secondary battery according to the present embodiment can exhibit excellent output characteristics, and is therefore suitable for use as a power source for driving EVs and HEVs.
[0089] [Method of manufacturing non-aqueous electrolyte secondary battery] The method for producing the nonaqueous electrolyte secondary battery according to the present embodiment is not particularly limited, but is preferably a method including preparing an electrode active material slurry and applying the electrode active material slurry to the surface of the current collector to form a coating film.
[0090] Hereinafter, an example of a preferred method for producing the nonaqueous electrolyte secondary battery according to this embodiment will be described.
[0091] First, the above-mentioned electrode active material, gel-forming polymer, and conductive assistant are mixed together with a solvent to prepare an electrode active material slurry.
[0092] The solvent is not particularly limited, and N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, methylformamide, cyclohexane, hexane, water, and the like can be used.
[0093] The method for preparing the electrode active material slurry by mixing the electrode active material, the gel-forming polymer, the conductive assistant, and the solvent is not particularly limited, and conventionally known knowledge regarding the order of addition of the components, the mixing method, and the like may be appropriately referred to.
[0094] The concentration of the electrode active material slurry is not particularly limited. However, from the viewpoint of facilitating the application of the slurry described below, the concentration of the total solid content relative to 100% by mass of the electrode active material slurry is preferably 35 to 75% by mass, more preferably 40 to 70% by mass. When the concentration is within the above range, an electrode active material layer having a sufficient thickness can be easily formed by application.
[0095] Next, the electrode active material slurry is applied onto a current collector and dried. After application, pressing may be performed as necessary.
[0096] The method for applying the electrode active material slurry to the current collector is not particularly limited, and examples thereof include a screen printing method, a spray coating method, an electrostatic spray coating method, an inkjet method, and a doctor blade method.
[0097] The coating thickness of the electrode active material slurry is appropriately set in consideration of the thickness of the electrode active material layer to be formed, and is preferably 200 to 2000 μm, more preferably 400 to 1000 μm.
[0098] The drying method after applying the electrode active material slurry on the current collector is not particularly limited, and may be any method that removes at least a part of the solvent. The drying method may include heating. The drying conditions (drying time, drying temperature, etc.) may be appropriately set depending on the volatilization rate of the solvent contained in the applied electrode active material slurry, the application amount of the electrode active material slurry, etc.
[0099] When pressing is performed, the pressing means is not particularly limited, and for example, a calendar roll, a flat plate press, or the like can be used.
[0100] In this manner, an electrode (positive or negative electrode) can be obtained.
[0101] After preparing the electrodes as described above, the electrodes and separators are laminated to prepare a power generating element. The method for preparing the power generating element is not particularly limited, and conventionally known knowledge may be appropriately referred to. As an example, a positive electrode and a negative electrode are laminated so as to face each other via a separator to prepare a unit cell layer. The unit cell layers are laminated until the desired number of layers are obtained, thereby obtaining a power generating element.
[0102] The positive electrode tab and the negative electrode tab are joined to the obtained power generating element by welding. If necessary, it is desirable to remove excess tabs and the like by trimming after welding. Although there is no particular limitation on the joining method, the joining is performed using an ultrasonic welding machine, which is superior in that it can prevent deterioration of the electrode active material layer (negative electrode active material layer and positive electrode active material layer) due to heat because it does not generate heat (heat) during joining and can be joined in an extremely short time. At this time, the positive electrode tab and the negative electrode tab can be arranged so as to face each other on the same side (same take-out side). This allows the positive electrode tabs of each positive electrode to be bundled together and taken out from the exterior body as one positive electrode current collector plate. Similarly, the negative electrode tabs of each negative electrode to be bundled together and taken out from the exterior body as one negative electrode current collector plate. In addition, the positive electrode current collector plate (positive electrode current collector tab) and the negative electrode current collector plate (negative electrode current collector tab) may be arranged so as to be on opposite sides (different take-out sides).
[0103] The obtained power generating element is covered with an exterior body. There are no limitations on the method for covering the power generating element with an exterior body, and conventionally known knowledge may be appropriately referred to. As an example, the power generating element is sandwiched between a laminate film used for the battery exterior body from above and below so that a positive electrode current collector plate (positive electrode current collector tab) and a negative electrode current collector plate (negative electrode current collector tab) can be taken out of the battery exterior body.
[0104] Next, three sides of the outer periphery (sealed portion) of the upper and lower laminate films are sealed by thermocompression. By sealing the three sides of the outer periphery by thermocompression, a three-sided sealed body is obtained. At this time, it is preferable to seal the heat-sealed portion of the side from which the positive electrode current collector plate (positive electrode current collector tab) and the negative electrode current collector plate (negative electrode current collector tab) are taken out. This is because if the positive electrode current collector plate and the negative electrode current collector plate are in the opening during the subsequent electrolyte injection, there is a risk that the electrolyte will splash out during the electrolyte injection.
[0105] Although a battery having a laminated structure has been described above, the battery is not limited to a laminated type, and various shapes such as a rectangular shape, a paper shape, a cylindrical shape, a coin shape, etc. can be adopted as the battery configuration.
[0106] Next, the electrolyte is injected into the three-side sealed body through the opening of the remaining side of the three-side sealed body by the injection device. This forms an electrolyte layer in which the separator is impregnated with the electrolyte. At this time, it is preferable to store the three-side sealed body in a vacuum box connected to a vacuum pump so that the electrolyte can be impregnated into the laminate inside the three-side sealed body, particularly the separator and the electrode active material layer, as quickly as possible. Furthermore, it is preferable to perform the injection in a state in which the pressure is reduced and the inside is in a high vacuum state. After the injection, the three-side sealed body is removed from the vacuum box, and the remaining side of the three-side sealed body is temporarily sealed. In this way, a laminate type (laminated structure) nonaqueous electrolyte secondary battery can be obtained in which unit cell layers are stacked so that the positive electrode and the negative electrode face each other via the separator.
[0107] [Battery pack] A battery pack is a device that consists of multiple batteries connected together. More specifically, it is a device that uses at least two batteries and is configured in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.
[0108] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. A large-capacity, high-output assembled battery suitable for a vehicle driving power source or an auxiliary power source that requires a high volumetric energy density and a high volumetric output density can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large-capacity assembled battery, can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.
[0109] [Transportation equipment] The nonaqueous electrolyte secondary battery of this embodiment has excellent output characteristics. Furthermore, it has a high volume energy density. In vehicle applications such as electric vehicles, hybrid electric vehicles, fuel cell vehicles, and hybrid fuel cell vehicles, higher capacity, larger size, and longer life are required compared to electric and portable electronic device applications. In addition, it is required to be compatible with rapid charging. Therefore, the nonaqueous electrolyte secondary battery can be mounted on transportation equipment. In particular, the nonaqueous electrolyte secondary battery can be suitably used as a power source for vehicles, for example, a power source for driving a vehicle or an auxiliary power source. Therefore, one embodiment of the present invention provides a transportation equipment equipped with the nonaqueous electrolyte secondary battery.
[0110] Specifically, a battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a long-life battery with excellent long-term reliability and output characteristics can be configured, and thus, by mounting such a battery, a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge can be configured. For example, if a battery or a battery pack formed by combining a plurality of batteries is used in a hybrid vehicle, a fuel cell vehicle, or an electric vehicle (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light vehicles, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles), the vehicle will have a long life and high reliability. However, the application is not limited to automobiles, and the battery pack can be applied to, for example, various power sources for other vehicles, such as trains, and can also be used as a mounted power source for an uninterruptible power supply device, etc. EXAMPLES
[0111] The present invention will be explained in more detail below using examples and comparative examples, but it is not limited to the following examples in any way.
[0112] [Production Example] <Preparation of negative electrode> A solid content consisting of 95.5 mass% graphite (average particle size: 20 μm) as the negative electrode active material, 0.5 mass% carbon black as the conductive assistant, and 4 mass% polyvinylidene fluoride (PVdF) as the binder was prepared. An appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to this solid content, and mixed at 2000 rpm for 6 minutes using a planetary stirring type mixing and kneading device "Awatori Rentaro" (ARE-310, manufactured by Thinky Corporation) to prepare a negative electrode slurry. The negative electrode slurry was uniformly applied to Cu foil placed on a smooth plate using a doctor blade so that the thickness of the negative electrode active material layer was 86 μm. Thereafter, it was dried for 2 hours on a hot plate heated to 80 ° C., resulting in a negative electrode active material mass (area weight of negative electrode active material) of 13 mg / cm. 2 The negative electrode active material layer had a porosity of 25%.
[0113] [Example 1] <Preparation of positive electrode> Positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1 A solid content consisting of 98% by mass of O2 (average particle size: 9 μm), 1% by mass of carbon nanotubes (fiber diameter: 1.6 nm, fiber length: 5 μm, aspect ratio: 3125) as a conductive assistant, and 1% by mass of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) (Kyner Flex 2501-10, manufactured by Arkema) as a gel-forming polymer was prepared. An appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to this solid content, and the mixture was mixed at 2000 rpm for 6 minutes using a planetary stirring type mixing and kneading device "Awatori Rentaro" (ARE-310, manufactured by Thinky Corporation) to prepare a positive electrode slurry. The positive electrode slurry was uniformly applied to an Al foil placed on a smooth plate using a doctor blade so that the thickness of the positive electrode active material layer was 62 μm. After that, it was dried for 2 hours on a hot plate heated to 80°C, and the positive electrode active material mass (weight of positive electrode active material) was increased to 20 mg / cm 2 The positive electrode active material layer had a porosity of 25%.
[0114] <Making a lithium-ion battery> The obtained positive electrode was placed on a 12 cm 2 , negative electrode 13cm 2 The laminate was cut so that it was. For the positive electrode, an aluminum foil with an Al terminal was laminated on the current collector foil side of the cut positive electrode. For the negative electrode, a copper foil with an Ni terminal was laminated on the current collector foil side of the cut negative electrode. A separator (manufactured by Celgard, made of PP) was inserted on the electrode active material layer side of the positive electrode and negative electrode to form a laminate. This laminate was sandwiched between heat-sealed aluminum laminate films, and a non-aqueous electrolyte obtained by dissolving Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI) 2mol / L in a mixed solvent of ethylene carbonate (EC) ethyl methyl carbonate (EMC) (volume ratio 3:7 (EC:EMC)) as a non-aqueous solvent was injected, and then vacuum sealed. In this way, a pouch-type lithium ion battery was produced in which the positive electrode and the negative electrode were laminated so as to face each other through the separator.
[0115] [Example 2] A lithium ion battery was produced in the same manner as in Example 1, except that in the production of the positive electrode, the compounding ratio of the components (positive electrode active material: conductive assistant: gel-forming polymer) was changed from 98:1:1 to 97.5:1:1.5.
[0116] In the prepared positive electrode, the mass of the positive electrode active material (weight per unit area of the positive electrode active material) was 20 mg / cm 2 The porosity of the positive electrode active material layer was 25%.
[0117] [Example 3] A lithium ion battery was produced in the same manner as in Example 1, except that in the production of the positive electrode, the compounding ratio of the components (positive electrode active material: conductive assistant: gel-forming polymer) was changed from 98:1:1 to 97:1:2.
[0118] In the prepared positive electrode, the mass of the positive electrode active material (weight per unit area of the positive electrode active material) was 20 mg / cm 2 The porosity of the positive electrode active material layer was 25%.
[0119] [Example 4] A lithium ion battery was produced in the same manner as in Example 1, except that in the production of the positive electrode, the compounding ratio of the components (positive electrode active material: conductive assistant: gel-forming polymer) was changed from 98:1:1 to 96:1:3.
[0120] In the prepared positive electrode, the mass of the positive electrode active material (weight per unit area of the positive electrode active material) was 20 mg / cm 2 The porosity of the positive electrode active material layer was 25%.
[0121] [Comparative Example 1] A lithium ion battery was produced in the same manner as in Example 1, except that in the production of the positive electrode, the compounding ratio of the components (positive electrode active material: conductive assistant: gel-forming polymer) was changed from 98:1:1 to 95:1:4.
[0122] In the prepared positive electrode, the mass of the positive electrode active material (weight per unit area of the positive electrode active material) was 20 mg / cm 2 The porosity of the positive electrode active material layer was 25%.
[0123] [Comparative Example 2] A lithium ion battery was produced in the same manner as in Example 1, except that in the production of the positive electrode, the compounding ratio of the components (positive electrode active material: conductive assistant: gel-forming polymer) was changed from 98:1:1 to 93:1:6.
[0124] In the prepared positive electrode, the mass of the positive electrode active material (weight per unit area of the positive electrode active material) was 20 mg / cm 2 The porosity of the positive electrode active material layer was 25%.
[0125] [Comparative Example 3] Positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1A solid content consisting of 96% by mass of O2 (average particle size: 9 μm), 2% by mass of acetylene black (AB) (average particle size 20 nm, secondary aggregate diameter: 50 nm, length: 3 μm, aspect ratio: 60) as a conductive assistant, and 2% by mass of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) (Kyner Flex 2501-10, manufactured by Arkema) as a gel-forming polymer was prepared. An appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to this solid content, and the mixture was mixed at 2000 rpm for 6 minutes using a planetary stirring type mixing and kneading device "Awatori Rentaro" (ARE-310, manufactured by Thinky Corporation) to prepare a positive electrode slurry. The positive electrode slurry was uniformly applied to an Al foil placed on a smooth plate using a doctor blade so that the thickness of the positive electrode active material layer was 62 μm. The mixture was then dried for 2 hours on a hot plate heated to 80 ° C. However, it was not possible to form a positive electrode.
[0126] [Comparative Example 4] A lithium ion battery was produced in the same manner as in Example 1, except that the following positive electrode was used as the positive electrode.
[0127] Positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1 A solid content consisting of 95% by mass of O2 (average particle size: 9 μm), 2% by mass of acetylene black (AB) (average particle size: 20 nm, secondary aggregate diameter: 50 nm, length: 3 μm, aspect ratio: 60) as a conductive assistant, and 3% by mass of polyvinylidene fluoride (PVDF) as a binder was prepared. An appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to this solid content, and the mixture was mixed at 2000 rpm for 6 minutes using a planetary stirring type mixing and kneading device "Awatori Rentaro" (ARE-310, manufactured by Thinky Corporation) to prepare a positive electrode slurry. The positive electrode slurry was uniformly applied to Al foil placed on a smooth plate using a doctor blade so that the thickness of the positive electrode active material layer was 62 μm. Thereafter, the mixture was dried for 2 hours on a hot plate heated to 80 °C, resulting in a positive electrode active material mass (area weight of positive electrode active material) of 20 mg / cm. 2 The positive electrode active material layer had a porosity of 25%.
[0128] [Output characteristic evaluation] The output characteristic evaluation was carried out by placing the lithium ion secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 2 and 4 in a thermostatic chamber (ARSF-0250-10, manufactured by Espec Corporation) set at 45°C. The lithium ion secondary battery prepared above was sandwiched between a 5 mm thick urethane rubber and a silicone sponge sheet, and was evaluated in a state where it was restrained at six points using a 10 mm thick metal plate and M6 screws. First, to confirm the capacity at a low rate, charge and discharge evaluation was performed twice at a cell voltage range of 2.5 to 4.3 V and a current value of 0.1 C rate. The capacity obtained at the 2.5 V cutoff during the second discharge was taken as the reference capacity of the cell. Next, after charging to 4.3 V at 0.1 C, discharge was performed at a 2 C rate, and the capacity obtained under the cell voltage 2.5 V cutoff condition was taken as the effective capacity. The 2 C effective capacity / reference capacity×100 obtained based on these values was taken as the 2 C effective capacity ratio (%). The results are shown in Table 1.
[0129] [Measurement of sheet resistance value] For the lithium ion secondary batteries produced in Examples 1 to 4 and Comparative Examples 1 to 2 and 4, the area resistance of the batteries was measured at a temperature of 25° C. by the following method.
[0130] First, the battery was fully discharged and then charged, and the voltage was checked and adjusted to SOC 50%. After that, it was discharged at 0.1C for 10 seconds. The DC resistance was measured from the current value I0.1C equivalent to 0.1C and the voltage change ΔV0.1C between the voltage after charging and the voltage after discharging. The resistance value (Ω) was then calculated according to Ohm's law from the measurement result of this DC resistance value. This was multiplied by the electrode area (area of the positive electrode active material layer) to obtain the sheet resistance value (Ω cm 2 The results are shown in Table 1.
[0131] [Table 1]
[0132] From the above results, it can be seen that the nonaqueous electrolyte secondary battery using the positive electrode of the embodiment of the present invention has a significantly reduced internal resistance (sheet resistance) (up to about 50%) compared to the comparative example battery, thereby significantly improving the output characteristics.
[0133] Furthermore, when comparing Examples 1 and 2 with Comparative Example 3, it can be seen that by using the conductive assistant of the present invention (fibrous carbon having an aspect ratio of 1000 or more), an electrode can be formed even with a smaller amount of gel-forming polymer. [Explanation of symbols]
[0134] 10a laminated secondary battery, 10b Bipolar secondary battery; 11 current collector, 11a: outermost current collector on the positive electrode side; 11b: an outermost current collector on the negative electrode side; 11' Positive electrode current collector 12 Negative electrode current collector 13 positive electrode active material layer, 15 negative electrode active material layer, 17 electrolyte layer, 19 cell layer, 21 Power generation elements, 23 Bipolar electrodes, 25 Positive current collector (positive tab), 27 negative electrode current collector (negative electrode tab), 29 Laminating film, 31 Sealing part.
Claims
1. A battery comprising: a positive electrode current collector; and a positive electrode active material layer that is a non-bonded body and is disposed on a surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, a conductive assistant, and a gel-forming polymer, The conductive additive is a fibrous carbon having an aspect ratio of 1000 or more, the gel-forming polymer is at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HEP), polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol dimethacrylate, polypropylene glycol diacrylate, and copolymers thereof; the content of the gel-forming polymer in the positive electrode active material layer is more than 0 mass% and less than 4 mass% with respect to 100 mass% of a total solid content, The positive electrode active material includes a lithium-transition metal composite oxide, a content of a conductive assistant in the positive electrode active material layer is more than 0 mass % and less than 2 mass % with respect to a total solid content of 100 mass %.
2. 2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of the gel-forming polymer in the positive electrode active material layer is 1 to 3 mass % relative to 100 mass % of the total solid content.
3. 3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of the gel-forming polymer in the positive electrode active material layer is 2% by mass or less with respect to 100% by mass of a total solid content.
4. 4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the gel-forming polymer is polyvinylidene fluoride-hexafluoropropylene (PVDF-HEP).
5. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the conductive assistant comprises fibrous carbon having an aspect ratio of 1000 or more.
6. 6. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the fibrous carbon is a carbon nanotube.
7. A positive electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 6, wherein the content of the conductive assistant in the positive electrode active material layer is 0.5 to 1.5 mass % relative to 100 mass % of the total solid content.
8. A positive electrode for a non-aqueous electrolyte secondary battery described in any one of claims 1 to 7, wherein the lithium-transition metal composite oxide is Li(Ni-Mn-Co)O 2 or an NMC composite oxide having a composition in which a portion of these transition metals is replaced by other elements.
9. A non-aqueous electrolyte secondary battery comprising the positive electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Gel-electrolyte-containing electrode and organic electrolyte cell using it
JP2004281162A
Secondary battery electrode, manufacturing method of the same, and secondary battery using the same
JP2005011660A
Nonaqueous secondary battery and method of manufacturing its anode
JP2006222073A
Lithium-ion battery
JP2017147222A
Nonaqueous electrolyte secondary battery
JP2020035634A